COVID-19 infection: comparing the knowledge, attitude and practices in a sample of nursing students - Provenzano, Sandro; Santangelo, Omar Enzo; Armetta, Francesco; Pesco, Giuseppina; Allegro, Alessandra; Lampasona, Maria; Terranova, Antonio; D'Anna, Giuseppe; Firenze, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background: SARS-CoV-2 infection is a global health problem that is primarily detected in Italy with progressive increase in cases and deaths. To facilitate the management of the pandemic in Italy, it is essential to understand the level of attention on COVID-19. The aim of the study was to evaluate the knowledge, attitude and practices towards SARS-CoV-2 among the nursing students of University of Palermo during the rapid rise period of the COVID-19 pandemic. Methods: The current study was a cross-sectional study. On-line questionnaires were used for the collection of the data by providing a survey in all nursing students. The questionnaire consisted of two parts: demographics and Knowledge, Attitude and Practices (KAP) survey. A multivariate linear regression model was used and adjusted Odds Ratios (aOR) are presented. Results: 525 students were interviewed and their mean age was 21.8. The overall score indicates good practices among the three courses of study (p=0.025). The Multivariable logistic regression showed that the dependent variable “Practice poor score” is statistically significant associated with these independent variables: “Other country of birth” (aOR 17.7, 95% CI 2.31-136.03), “second” (aOR 2.65, 95% CI 1.21-7.80) and “third” (aOR 2.96, 95% CI 1.31-6.72) year of study, “low perceived health status”(aOR 2.35, 95% CI 1.04-5.30) and “Knowledge poor score (aOR 3.05, 95% CI 1.06-8.77). Conclusion: Our results suggest that health education programs aimed at improving COVID-19 knowledge are helpful for nursing students to hold optimistic attitudes and maintain appropriate practices.